Building a Sustainable Work Culture: The Mediating Role of Psychological Capital in SME Performance - Tri Melda Mei Liana; Anita Tresia Samosir; Sunday Ade Sitorus; Hendrik Samosir (International Journal of Applied Business and International Management, 2026)
Growing sustainability pressures have increased the importance of internal capabilities for micro, small, and medium enterprises (MSMEs) to achieve sustainable performance, especially in resource-constrained environments. This study examines the effects of sustainable human resource management (Sustainable HRM) and psychological capital (PsyCap) on sustainable performance, with sustainable work culture as a mediating variable. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) based on data from 105 MSME owners in Medan City. The results show that a sustainable work culture has a significant positive effect on sustainable performance (? = 0.462, t = 4.658, p 0.001). PsyCap does not significantly influence sustainable work culture (? = –0.202, p = 0.122) or sustainable performance (? = –0.093, p = 0.369). Sustainable HRM shows no significant effect on performance (? = 0.031, p = 0.720) and negatively affects work culture (? = –0.324, p 0.001). The findings indicate that organizational culture plays a key role in shaping sustainability in MSMEs, suggesting that cultural alignment may be more influential than formal HR practices or individual psychological traits. These results offer practical and policy implications by emphasizing targeted capacity-building programs and supportive interventions to strengthen MSMEs’ internal capabilities.